Разработка эффективных методов оптимизации сложных теплоутилизационных систем энергетических установок (часть 2) - Фиалко, Н. М.; Степанова, А. И.; Навродская, Р. А. (Енергетика і автоматика, 2017)
DEVELOPMENT OF EFFECTIVE METHODS OPTIMIZATION COMPLEX HEAT RECOVERY SYSTEMS ENERGY INSTALLATIONS (PART 2) N. Fialko, А. Stepanovа R. Navrodska The problem of developing and implementing efficient technologies for utilizing the heat of waste gases from power plants is an important part of the general problem of modernizing Ukraine’s energy sector. Prices for natural gas in Ukraine are now continuously increasing. This determines the need for the introduction of new energy-efficient technologies in all spheres of the national economy, including in the sphere of industrial and municipal heat and power engineering. For many power plants, the heat of the waste gases represents the bulk of the heat losses. So heat loss with waste gases in boiler units is about 17%, in industrial furnaces - up to 25% ... 35%. In the context of a shortage of energy resources, Ukraine’s energy sector is in need of introducing efficient heat recovery equipment, developed using modern effective optimization methods. The situation that has developed in the energy sector of Ukraine determines the relevance of the works devoted to the implementation of various energy saving directions. This also applies to the direction associated with increasing the efficiency of heat recovery technologies. In Part 1 of this work, based on the principles of the structural-variant approach to optimization, an optimization method for complex heat recovery systems of boiler units was developed. The second part of the work is devoted to the development for the boiler plants and glass melting furnaces of an optimization method based on the principles of multi-level optimization. Three heat recovery systems are considered: the heat recovery system of a glass melting furnace intended for preheating air, a heat recovery system for heating the boiler’s return water and a heat recovery system for a boiler house with a combined utilization of the utilized heat. Examples of these systems have developed the main stages of the method, based on the principles of multi-level optimization. The basic principles of multilevel optimization are as follows: • to divide the heat recovery system into several levels of optimization; • reduce a complex multicriteria and multiparameter optimization problem to simpler local problems of each level; • when constructing a mathematical model of a given level, use variable parameters of an object of a given level as variables; • use as optimal parameters optimal parameters that are the results of solving local optimization problems of other levels; • use a scheme of recursive traversal of optimization levels; • At each level of optimization, solve the corresponding optimization task and determine the optimal values of the parameters; • refine the obtained optimal parameters with the help of additional iterations. In accordance with these principles of multi-level optimization, the heat-recovery systems under investigation are divided into several levels of optimization. The block diagrams of multilevel optimization and schemes of recursive traversal of optimization levels have been developed. Methods for constructing mathematical models, recursive target optimization functions, and variable parameters for each level of optimization are chosen. Optimal parameters of the systems are determined. The scheme of recursive traversal of optimization levels allows for a constant information exchange between optimization levels. If necessary, the scheme of recursive traversal of optimization levels provides for branching at the upper level, which provides, under certain conditions, the termination of recursion. Also, a scheme for recursive traversal of levels provides for branching at other levels to enable parallel recursions. In this case, several recursive calls are made on one recursive branch. As an example, the optimal values of the regime and design parameters for the heat recovery system of the glass melting furnace and the unitized heat recovery unit for the boiler houses with combined utilization of the utilized heat are given. The use of the obtained optimum values of the regime and design parameters in the development of the design of the heat recovery system for the glass melting furnace makes it possible to increase the efficiency of the furnace by 5-10% and, accordingly, to reduce the heat losses. Comparative analysis of the developed optimization methods has shown that using the method based on the principles of multi-level optimization allows to take into account practically all technical losses in the heat recovery system and to optimize a greater number of parameters than using the method based on the principles of the structural-variant approach. In addition, the efficiency of heat recovery systems optimized using a method based on the principles of multi-level optimization is 2-3% higher than the efficiency of the same systems optimized using the structural-variant approach.